2020
DOI: 10.1039/d0cy01254h
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface properties in CO2 methanation over carbon-supported Ni catalysts and their promotion by Fe

Abstract: The surface chemistry of the activated carbon supporting material was tailored to investigate the influence of O and N groups as well as O-free Lewis basic sites on the performance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…In this sense, and in line with the remarks made above, the BCCe30Ni20 catalysts clearly exhibited the best catalytic performance. The best Ni loading of 20 wt.% is in agreement with the results reported in previous studies for Ni-based catalysts supported on different materials [6,15].…”
Section: Effect Of Nickel Loadingsupporting
confidence: 91%
See 1 more Smart Citation
“…In this sense, and in line with the remarks made above, the BCCe30Ni20 catalysts clearly exhibited the best catalytic performance. The best Ni loading of 20 wt.% is in agreement with the results reported in previous studies for Ni-based catalysts supported on different materials [6,15].…”
Section: Effect Of Nickel Loadingsupporting
confidence: 91%
“…The reaction is highly exothermic and generally carried out in the temperature range of 200−500 • C. However, CO 2 conversion toward CH 4 involves high activation energies, which make the reaction less likely at relatively low temperatures [6]. Therefore, the use of an appropriate catalyst is mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon is another type of support in heterogeneous catalysis, which has been deemed as inactive regarding CO2 methanation when using Ni-based catalysts [72]. However, Gonçalves et al [73] managed to improve the performance of activated carbon (AC) supported Ni catalysts by modifying the surface chemistry of carbon and by introducing Fe as a second metal. They reported that 5% Fe addition on a 15% Ni catalyst supported on activated carbon with increased basicity (AC-R) improved the catalytic performance Carbon is another type of support in heterogeneous catalysis, which has been deemed as inactive regarding CO 2 methanation when using Ni-based catalysts [72].…”
Section: Promotion With Fementioning
confidence: 99%
“…They reported that 5% Fe addition on a 15% Ni catalyst supported on activated carbon with increased basicity (AC-R) improved the catalytic performance Carbon is another type of support in heterogeneous catalysis, which has been deemed as inactive regarding CO 2 methanation when using Ni-based catalysts [72]. However, Gonçalves et al [73] managed to improve the performance of activated carbon (AC) supported Ni catalysts by modifying the surface chemistry of carbon and by introducing Fe as a second metal. They reported that 5% Fe addition on a 15% Ni catalyst supported on activated carbon with increased basicity (AC-R) improved the catalytic performance for CO 2 methanation.…”
Section: Promotion With Fementioning
confidence: 99%
See 1 more Smart Citation